A New Path for Developing Academic Abilities of Indonesian Chinese Learners in The Era of Artificial Intelligence - Stephanie Phanata (Sinolingua: Journal of Chinese Studies, 2025)
This article focuses on the application of Artificial Intelligence (AI) technology in International Chinese language education and its impact on the development of Chinese language professionals. Specifically, it explores the opportunities and challenges facing Chinese language majors in Indonesia, focusing on the “academic breakthrough” challenges faced by these learners. This research is significant in that it integrates cutting-edge technologies such as natural language processing to address the real challenges of digital transformation in education, focusing specifically on innovations in Chinese language education in non-native contexts, particularly in Indonesia. Employing a theoretical approach, the study uses case studies, teaching experiments, and questionnaires to evaluate the effectiveness of intelligent tutoring systems, a “dual-teacher” teaching model, and intelligent writing training tools in Chinese language instruction at Indonesian universities. Preliminary findings suggest that personalized learning powered by AI can significantly improve learning motivation and language production quality, particularly in academic writing. However, insufficient digital academic literacy among teachers and students can limit the effectiveness of technology applications. The conclusion suggests that international Chinese education should promote the deep integration of language instruction and digital literacy, strengthen teacher training in intelligent educational technologies, and build a new “human-computer collaborative” teaching ecosystem to provide a sustainable path to achieving educational equity and academic breakthroughs.